Analysis of microlayer defects of a functionally graded titanium alloy by electrical discharge machining - Abdulkareem, Sulaiman; Khan, Ahsan Ali; Konneh, Mohamed (Khon Kaen University,Thailand, 2018)
This paper reports on the surface characteristics of a functionally graded Titanium (Ti-6Al-4V) alloy during Electrical Discharge Machining (EDM). The electrical discharge input parameters employed for this work are current (I), on-time (Ton), off-time (Toff) and spark gap voltage (V). The electrode used for EDM of the titanium workpieces is an electrolytic copper electrode. The two machining processes employed are at room temperature and sub-zero temperature using liquid nitrogen at -1600C as electrode coolant during the process. EDM machining was designed for all the input parameters and the materials machined with three different currents, i.e., 4.5A, 5.5A and 7.5A, while the workpieces were examined for microlayer defects using scanning electron microscopy (SEM). The result showed an average micro-layer thickness of 24.47 μm with current of 7.5A when machined at -1600C. Also an increase in crack formation with the highest current of 7.5A for the surfaces machined at subzero temperature was recorded for both the workpieces and electrode materials.